PPM1D Mosaic Truncating Variants in Ovarian Cancer Cases May Be Treatment-Related Somatic Mutations. (27th January 2016) - Pharoah, Paul D. P.; Song, Honglin; Dicks, Ed; Intermaggio, Maria P.; Harrington, Patricia; Baynes, Caroline; Alsop, Kathryn; ,; Bogdanova, Natalia; Cicek, Mine S.; Cunningham, Julie M.; Fridley, Brooke L.; et al.
Abstract: Mosaic truncating mutations in the protein phosphatase, Mg 2+ /Mn 2+ -dependent, 1D ( PPM1D ) gene have recently been reported with a statistically significantly greater frequency in lymphocyte DNA from ovarian cancer case patients compared with unaffected control patients. Using massively parallel sequencing (MPS) we identified truncating PPM1D mutations in 12 of 3236 epithelial ovarian cancer (EOC) case patients (0.37%) but in only one of 3431 unaffected control patients (0.03%) ( P = .001). All statistical tests were two-sided. A combination of Sanger sequencing, pyrosequencing, and MPS data suggested that 12 of the 13 mutations were mosaic. All mutations were identified in post-chemotherapy treatment blood samples from case patients (n = 1827) (average 1234 days post-treatment in carriers) rather than from cases collected pretreatment (less than 14 days after diagnosis, n = 1384) ( P = .002). These data suggest that PPM1D variants in EOC cases are primarily somatic mosaic mutations caused by treatment and are not associated with germline predisposition to EOC.